(untitled) (Economics and region, 2020)
The purpose of the article is to study the features of animation as a factor in the formation of the competitive advantages of organized tourism services. The authors determined that animation is used in many areas of tourism and organized leisure, including in the form of animation programs, theatrical performances, animation in theme parks, sports and hotel animation. The article explores the main approaches to defining the essence of the concept of "animation". It is noted that animation is the process of organizing leisure time in recreation and recreation establishments, at corporate events and MICE events, in children’s camps and children’s parties, which provides for the personal participation of vacationers in animation activities. As a result of the research, the main components of animation were identified, which characterize its content as a type of organized tourist leisure: the culture of consumption; self-education; informal communication; cultural and creative activities; meeting environmental needs (communication with flora and fauna); health and fitness classes; entertainment activities and the like. The types of tourist animation based on various classification criteria are analyzed. The component of animation activity in the socio-cultural life of a person is expressed in the experience, impression, emotion, state, covering the tourist during the rest. Based on these reactions, the tourist feels, comprehends the perception of the event, evaluates the quality of rest and services provided. Forms of animation events: entertaining, exciting, spectacular events, relaxing procedures, active outdoor games, family and calendar holidays, anniversaries with friends, communicating with pleasant people in an unusual atmosphere, communicating with animals, traveling, etc. Thus, animation as a component of leisure is a way of initiating a person’s creative needs and social activity; optimization of interpersonal and intergroup relations, socio-cultural integration, self-awareness and self-determination of the individual in the context of building a civil society. Prospects for further research are the identification of potential directions for the development of animation in the field of tourism, improving its quality and service, taking into account the needs of modern consumers of a tourist product.